Strangers No More: Collaborative Inquiry Through Narrative as Teacher Reflective Practice (LEARNing Landscapes, 2021)
Two teachers and a professor engaged in collaborative inquiry through narrative as a form of reflective practice, pedagogical growth, and practitioner research. Using a Deweyan lens and elements of narrative inquiry, we consider our stories of teaching through a supportive, growth-based sharing process. Viewing pedagogical experiences through this lens enabled us to enter each other’s worlds and engage in reflection—together. Our work speaks to the situations that arise when expectations conflict with reality. The process of reflecting and re-reflecting led us to the conclusion that engagement in this fashion is a valuable reflexive method for teacher professional growth.
Keywords: narrative; reflective practice; practitioner inquiry; professional growth